Comparative study to identify the safety, effectiveness and ease of obstetric forceps for delivery of floating head in cesarean section - Ingole, Sonali Jitendra; Manwani, Saloni (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Background: Difficulty is frequently encountered in extraction of floating fetal head. This study will focus on comparison of Forceps assisted fetal head extraction during Lower segment caesarean section (LSCS) with manual method of extraction in LSCS. Methods: The ANC patients attending antenatal OPD and admitted for elective caesarean section fulfilling the inclusion criteria were randomly divided into two groups each of 400 patients: Group 1 of patients undergoing manual extraction of fetal head during LSCS; and Group 2 consisting of patients with forceps assisted delivery of fetal head in LSCS. Following factors will be evaluated in patients: maternal blood loss, any extension of uterine incision, difference in pre and post op hemoglobin levels of the patient and Apgar score of baby at 1 and 5 minutes. Results: Patients in both the groups were matched demographically. The demographic variables such as maternal age, weight, parity and MGA (Mean Gestational age) were comparable in both the groups. Blood loss was significant in Group 1 (manual delivery) as compared with Forceps assisted delivery. This is also reflected in difference in pre and post op Hemoglobin levels. Although baby outcome in terms of Apgar score was similar in both groups, however morbidity in terms of uterine artery trauma, extension of uterine incision was much less in group 2 (Forceps assisted LSCS delivery) Conclusions: Although there was no statistically significant difference in outcome of babies (APGAR score), complication(s) were less (blood loss, uterine artery trauma) in Forceps assisted LSCS delivery group. Proper selection of patient(s), early anticipation for application for Forceps can help for better outcome of caesarean delivery.